EFFECTIVENESS OF A SUPPORTIVE INTERVENTION PROGRAM ON QUALITY OF LIFE AFTER AESTHETIC BLEPHAROPLASTY USING THE GLASGOW BENEFIT INVENTORY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate quality-of-life improvement after aesthetic blepharoplasty using the Glasgow Benefit Inventory (GBI) and to assess the effectiveness of a supportive intervention program in enhancing postoperative outcomes.Methods: A controlled interventional study was conducted on 150 patients undergoing aesthetic blepharoplasty at the Department of Plastic and Reconstructive Surgery, Hanoi Medical University Hospital, from December 2023 to February 2025. Participants were allocated into intervention and control groups, with 75 patients in each group. The intervention group received a standardized supportive care program including preoperative counseling, expectation management, postoperative care instructions, and scheduled follow-up monitoring. Quality of life was assessed using the GBI at 1 month and 3 months after surgery.Results: The intervention group had significantly higher GBI scores than the control group at both 1 month (27.3±17.2 vs. 21.1±17.6; p=0.012) and 3 months (43.7±19.1 vs. 34.7±21.8; p=0.002). General benefit and social support domains improved significantly more in the intervention group at both follow-up time points (p
Keywords: aesthetic blepharoplasty, Glasgow Benefit Inventory, quality of life, patient satisfaction, supportive intervention